2015
DOI: 10.1002/pssb.201552036
|View full text |Cite
|
Sign up to set email alerts
|

Inducing out‐of‐plane auxetic behavior in needle‐punched nonwovens

Abstract: We describe here a heat-compression protocol used on needlepunched commercial nonwoven fabrics which induces an out-of-plane auxetic response in these treated fabrics. The as-received samples, however, are not auxetic and show a decrease in thickness when stretched uniaxially. Using micro-CT imaging it was found that the vertical fiber bundles/columns, produced in the needle punching step of fabric manufacture, are tilted and buckled as a result of the heat-compression treatment. It is suggested that it is lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 44 publications
6
79
1
Order By: Relevance
“…Auxetic non-woven fabrics: Verma P et al [64] reported that it is possible to induce out-of-plane auxetic behavior in needlepunched nonwovens. They obtained needle-punched nonwoven fabrics from Ten Cate Protective Fabrics (Senoia, Georgia, USA).…”
Section: Citationmentioning
confidence: 99%
See 2 more Smart Citations
“…Auxetic non-woven fabrics: Verma P et al [64] reported that it is possible to induce out-of-plane auxetic behavior in needlepunched nonwovens. They obtained needle-punched nonwoven fabrics from Ten Cate Protective Fabrics (Senoia, Georgia, USA).…”
Section: Citationmentioning
confidence: 99%
“…Diagram showing the processing treatment of as-received samples in a Carver1 hot press to produce compressed" and "heat compressed" samples [64]. needle-punched nonwoven specimens tested along the machine direction.…”
Section: Figure 29mentioning
confidence: 99%
See 1 more Smart Citation
“…Auxetic non-woven fabrics: Verma P et al 64 reported that it is possible to induce out-of-plane auxetic behavior in needle-punched nonwovens. They obtained needle-punched nonwoven fabrics from Ten Cate Protective Fabrics (Senoia, Georgia, USA).…”
Section: Auxetic Knitted Fabrics Developed Based On Rotating Rectanglesmentioning
confidence: 99%
“…Induced out‐of‐plane auxetic behavior in needle‐punched commercial nonwoven fabrics is studied by Prateek Verma, Meisha L. Shofner, Angela Lin, Karla B. Wagner, and Anselm C. Griffin in their very interesting experimental paper . They describe a heat‐compression protocol used in the treated fabrics.…”
mentioning
confidence: 99%